Um algoritmos distribuído para escalonamento de sensores em RSSF - Matos, Daniel Ribeiro (2016)
Wireless Sensor Networks (WSNs) are used in a lot of applications: from smart homes to military enviromnets. In general, WSNs has severe energy restrictions - a sensor usualy has a limited batery and it’s not replaceable. Distributing the sensor in a random mander can lead to a redundancy of some areas and this is desirable to support fail of some sensors. In this work, we propose an distributed algorithm to schedule active sensors to reduce the redundancy of data obtainned by the network and prolong the network lifetime.